Electron spectroscopy of rare-gas clusters irradiated by x-ray free-electron laser pulses from SACLA. (8th January 2016) - Fukuzawa, H; Tachibana, T; Motomura, K; Xu, W Q; Nagaya, K; Wada, S; Johnsson, P; Siano, M; Mondal, S; Ito, Y; Kimura, M; Sakai, T; et al.
Abstract: We have measured electron energy spectra and asymmetry parameters of Ar clusters and Xe clusters illuminated by intense x-rays at 5 and 5.5 keV. A velocity map imaging spectrometer was developed for this purpose and employed at an x-ray free-electron laser facility, SACLA in Japan. The cluster size dependence and the peak fluence dependence of the electron spectra and asymmetry parameters are discussed.